Homer's First Battle Supplication and the End of Virgil's Aeneid - Fratantuono, Lee (Acta Classica Universitatis Scientiarum Debreceniensis, 2022)
One of the less appreciated literary influences on the Virgilian depiction of Aeneas' decision to slay Turnus at the end of the Aeneid is the first battle supplication scene in Homer's Iliad, the encounter of Adrestus with Menelaus and Agamemnon. Close consideration of Virgil's response to the Homeric scene sheds light on the poet's concerns in his presentation of the choice his Trojan hero Aeneas confronts in light of Turnus' appeal. Acrostics at the end of the Aeneid invite further reflection.